Fas Ligand+ Fallopian Tube Epithelium Induces Apoptosis in Both Fas Receptor+ T Lymphocytes and Endometrial Cells - Imarai-Bahamonde, C; Maisey-Munoz, K; Reyes-Lopez, F (2013)
Objective: To establish whether human fallopian tube (FT) epithelium can induce apoptosis in T lymphocytes and endometrial cells. Design: Laboratory-based study. Setting: Hospital. Patient(s): Women undergoing abdominal hysterectomy for FT samples, and women volunteers with and without endometriosis for endometrial biopsies. Intervention(s): FT samples obtained at time of surgery performed in reproductive-aged women with normal menstrual cycles. Main Outcome Measure(s): T lymphocytes or endometrial cells coincubated with FT epithelial cells and assayed for apoptosis by DNA nick-end labeling and caspase-3 activity, with the presence of Fas ligand (FasL) and Fas receptor (FasR) assessed by indirect immunostaining. Result(s): The epithelium of the FT-induced apoptosis in T cells as well as in human endometrial cells. The mechanism probably involves the FasL/FasR system; accordingly, we observed FasL at the apical surface of the epithelium and in the stroma of the FT at all phases of the menstrual cycle except during the early proliferative phase. The endometrial samples from patients with endometriosis did not express FasR and were resistant to apoptosis. Conclusion(s): In both FasR+ T lymphocytes and endometrial cells, FasL+ FT cells induce apoptosis. Data suggest that the FT epithelium acts as a barrier to limit the influx of lymphocytes as well as endometrial cells ascending the tube. Failure of these regulatory mechanisms may be related to the development of endometriosis. Copyright © 2013 American Society for Reproductive Medicine, Published by Elsevier Inc.